An interview analysis of coordination behaviours in Out–of–Hours secondary care. (November 2019) - Martindale, Sarah; Golightly, David; Pinchin, James; Shaw, Dominick; Blakey, John; Perez, Iker; Sharples, Sarah
Abstract: This paper seeks to elicit and structure the factors that shape the execution and, in particular, the coordination of work in Out of Hours care. Evenings and weekends in UK hospitals are managed by specific Out of Hours (OoH) care arrangements, and associated technology. Managing care within the constraints of staff availability and demands is a key concern for both patient care and staff wellbeing, yet has received little attention from healthcare human factors. A study of sixteen clinical staff used Critical Decision Method to understand how work is coordinated and the constraints and criteria that are applied by the roles managing OoH care. The analysis identified ten types of coordination decision that, in turn, underpinned three types of adaptive behaviour – pre-emption, information augmentation and self-organisation – that were crucial for the effective performance in OoH care. These behaviours explain how OoH staff manage the task demands placed on them, individually and as a team. Highlights: Decision-making analysis of the coordination of Out of Hours care, a critical aspect of secondary healthcare. Actors try and pre-empt peaks in workload by building an understanding of clinical staff load and availability. Additional, bi-directional information flows to supplement gaps in information supported by technology. Actors take on unexpected tasks, hidden from task management tool, such as self-organising and additional care duties.